THE ANALYSIS OF BLOOD DEFECTION AND ITS COMPONENTS IN SYSTEM OF MEASURES FOR THE PREVENTION OF INFECTION WITH TRANSFUSION AND TRANSMISSIBLE INFECTIONS - Tashtemirov, Kamal; Imangazinov, Sagit; Tashtemirova, Olga; Imangazinova, Saule (European Scientific Journal, ESJ, 2014)
When carrying out a monitoring of defection of a donor blood it is established that absolute defection of a blood and its components was enlarged by 3,9 times. Thus paid donors make 7,6%, and gratuitous 92,4% of total number of absolute defection. The share of infections in structure of absolute defection averages 47,6%. Frequency of occurrence of transfusion and transmissible infections among donors makes 0,6%. Antibodies of HCV, HBS Ag, Luis in 10 times more often are taped at primary donors, than at the repeated.